THE ROLE OF DIGITAL IN EARLY CHILDHOOD ISLAMIC EDUCATION - Husin Husin; Santi; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
We are currently in an era where almost everyone is familiar with technology and everything is completely connected. With the advancement of digital technology now, every parent needs to keep updating information and learning how to educate their children, especially Islamic religious knowledge in today's digital era. Children must be instilled with Islamic religious values ​​so that they can get used to doing good, taking action and making decisions in their lives based on Islamic religious values ​​which serve as guidelines until adulthood. In order to avoid the negative effects of the internet, the role of parents is very important in accompanying children to learn, especially when they are playing and learning to use gadgets. Therefore, This study aims to find out how today's parents provide Islamic education by utilizing digital technology. This research is a library research using the mass media method. Research results have found the large role of digital in helping provide Islamic education to early childhood. In early childhood education, the inculcation of religious values ​​is intended so that children can know God, imitate worship movements, say prayers, recognize good and bad behavior, and get used to good behavior. By utilizing digital tools in the learning process, parents will find it easier to provide understanding to children and can make children more enthusiastic, active and creative. This research is a library research using the mass media method. Research results have found the large role of digital in helping provide Islamic education to early childhood. In early childhood education, the inculcation of religious values ​​is intended so that children can know God, imitate worship movements, say prayers, recognize good and bad behavior, and get used to good behavior. By utilizing digital tools in the learning process, parents will find it easier to provide understanding to children and can make children more enthusiastic, active and creative. This research is a library research using the mass media method. Research results have found the large role of digital in helping provide Islamic education to early childhood. In early childhood education, the inculcation of religious values ​​is intended so that children can know God, imitate worship movements, say prayers, recognize good and bad behavior, and get used to good behavior. By utilizing digital tools in the learning process, parents will find it easier to provide understanding to children and can make children more enthusiastic, active and creative. Instilling religious values ​​is intended so that children can know God, imitate worship movements, say prayers, recognize good and bad behavior, and get used to good behavior. By utilizing digital tools in the learning process, parents will find it easier to provide understanding to children and can make children more enthusiastic, active and creative. Instilling religious values ​​is intended so that children can know God, imitate worship movements, say prayers, recognize good and bad behavior, and get used to good behavior. By utilizing digital tools in the learning process, parents will find it easier to provide understanding to children and can make children more enthusiastic, active and creative.